2016
DOI: 10.5152/tjar.2016.09483
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Clinical Effects of Dexketoprofen and Paracetamol Used for Analgesia in Endoscopic Retrograde Cholangiopancreatography

Abstract: Objective: This study aimed to compare 50 mg dexketoprofen vs. 1 g paracetamol that were parenterally administered before endoscopic retrograde cholangiopancreatography (ERCP) under sedoanalgesia with comparable anaesthesia depth regarding haemodynamic, pain, narcotic analgesic requirement, recovery and post-procedural cognitive functions. Methods:Overall, 80 ASA I-III patients aged 18-75 years who were undergoing scheduled ERCP were randomly assigned into three groups. In all patients, the mini-mental test (M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Postoperative pupillary center displacement is considered for two reasons: Firstly, pupils constrict due to the anti-mydriatic effect of brimonidine, which conduct to slight displacement of pupil center. Studies have found a correlation between pupillary excursion (the distance from the center of the pupil to the center of the cornea) and dark pupil diameter, which increases pupillary excursion when pupil diameter is increased by changing lighting conditions from photopic to mesopic, the displacement increased with the pupil diameter of the subjects ( 24 , 25 ). The second reason is that vault changes with the pupil, which has certain mechanical stimulation to the iris tissue, resulting in subtle changes in the pupil center.…”
Section: Discussionmentioning
confidence: 99%
“…Postoperative pupillary center displacement is considered for two reasons: Firstly, pupils constrict due to the anti-mydriatic effect of brimonidine, which conduct to slight displacement of pupil center. Studies have found a correlation between pupillary excursion (the distance from the center of the pupil to the center of the cornea) and dark pupil diameter, which increases pupillary excursion when pupil diameter is increased by changing lighting conditions from photopic to mesopic, the displacement increased with the pupil diameter of the subjects ( 24 , 25 ). The second reason is that vault changes with the pupil, which has certain mechanical stimulation to the iris tissue, resulting in subtle changes in the pupil center.…”
Section: Discussionmentioning
confidence: 99%